Mechanism of Ershen Zhenwu Decoction in ameliorating chronic heart failure via JNK/MAPK-regulated apoptosis: insights from network pharmacology and experimental validation - Liu, Yulong; Wang, Xinyue; Zhang, Maomao; Cheng, Dan; Zhu, Zhenpeng; Ge, Lan; Cheng, Xiaoyu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic heart failure (CHF) is a complex cardiovascular disease caused by different pathological mechanisms. Modern medicine has made advancements in CHF treatment; however, there are still many challenges. Ershen Zhenwu Decoction (ESZWD) is a Xin'an medicine that has been clinically applied for years and had good efficacy against CHF; however, its underlying mechanisms remain undetermined. Therefore, this study aims to investigate the primary molecular mechanisms of ESZWD in CHF treatment and elucidate its multi-target and multi-level mode of action.ObjectiveThe aim of this study was to investigate the main molecular mechanisms of ESZWD for the treatment of CHF and to elucidate its multi-target and multi-level mode of action.MethodsThis study employed a network pharmacology approach to analyze the main ESZWD components and core targets. Furthermore, primary CHF targets were predicted to develop a protein–protein interaction (PPI) network and perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Moreover, molecular docking was carried out to validate the binding between active ingredients and key targets. For in vitro studies, myocardial cell injury models were employed, and immunofluorescence, RT-qPCR, Western blot, and flow cytometry were carried out to validate the critical targets of relevant signaling pathways and the specific ESZWD regulatory mechanisms.ResultsNetwork pharmacology identified 437 targets for 34 major ESZWD components. Of these, 216 drug–disease intersection targets were identified. The PPI network analysis identified the following core targets: STAT3, HSP90AA1, MAPK8, NFKB1, HIF1A, MMP9, PTGS2, BCL2L1, TLR4, and ESR1. GO analysis revealed that these targets were associated with exogenous stimuli responses, phosphorylation regulation, inflammatory response, and protein tyrosine kinase activity. Furthermore, KEGG analysis showed that ESZWD predominantly impacts cancer, inflammatory response, and apoptosis pathways, with c-Jun N-terminal kinase/mitogen-activated protein kinase (JNK/MAPK)-regulated apoptosis being a key pathway. In vitro analyses revealed that ESZWD effectively inhibited JNK activation, modulated MAPK signaling, downregulated pro-apoptotic gene expression, and significantly reduced cardiomyocyte apoptosis rates, thus validating the network pharmacology findings.ConclusionOur study shows that paeoniflorin, acetylaconitine, and cryptotanshinone bind to key proteins in the JNK/MAPK apoptosis pathway. In vitro validation confirms drug serum from ESZWD regulates this pathway, supporting its therapeutic potential for CHF.